2008
DOI: 10.1111/j.1467-7652.2008.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of an acyl‐CoA‐dependent diacylglycerol acyltransferase 1 (DGAT1) gene from Tropaeolum majus, and a study of the functional motifs of the DGAT protein using site‐directed mutagenesis to modify enzyme activity and oil content

Abstract: SummaryA full-length cDNA encoding a putative diacylglycerol acyltransferase 1 (DGAT1, EC seed-specific expression of TmDGAT1 was able to complement the low TAG/unusual fatty acid phenotype of the Arabidopsis AS11 ( DGAT1 ) mutant. Over-expression of TmDGAT1 in wild-type Arabidopsis and high-erucic-acid rapeseed (HEAR) and canola Brassica napus resulted in an increase in oil content (3.5%-10% on a dry weight basis, or a net increase of 11%-30%). Site-directed mutagenesis was conducted on six putative functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(171 citation statements)
references
References 72 publications
(121 reference statements)
16
154
1
Order By: Relevance
“…In Arabidopsis, AtDGAT1 controls TAG biosynthesis in developing seeds, whereas AtDGAT2 seems to have no obvious phenotype functionally (Shockey et al 2006;Zhang et al 2009). Similarly, the DGAT1s significantly regulate TAG accumulation in maize (Zheng et al 2008), Tropaeolum majus L. (Xu et al 2008) and soybean (Li et al 2010b). Further, studies have shown that the DGAT2s play a critical role in the accumulation of unusual FAs (such as epoxy and hydroxy fatty acids) in castor bean (Kroon et al 2006), tung tree (Shockey et al 2006) and Vernonia (Li et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, AtDGAT1 controls TAG biosynthesis in developing seeds, whereas AtDGAT2 seems to have no obvious phenotype functionally (Shockey et al 2006;Zhang et al 2009). Similarly, the DGAT1s significantly regulate TAG accumulation in maize (Zheng et al 2008), Tropaeolum majus L. (Xu et al 2008) and soybean (Li et al 2010b). Further, studies have shown that the DGAT2s play a critical role in the accumulation of unusual FAs (such as epoxy and hydroxy fatty acids) in castor bean (Kroon et al 2006), tung tree (Shockey et al 2006) and Vernonia (Li et al 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast strains H1246 and INVSc1 harboured the p426-GAL empty vector and were used as negative and positive controls. Transformants were selected and expression of the recombinant genes in yeast was induced as previously described (Xu et al 2008). After induction, cultures were grown at 30 C, 250 rpm.…”
Section: Heterologous Expression and Fatty Acid Substrate Feeding In mentioning
confidence: 99%
“…In addition, similar sequence features have been reported in other plants, such as A. thaliana, V. fordii, E. pitardii, and Tropaeolum majus. [17,18,26,28] …”
Section: Cloning and Sequence Analysis Of The Maize Dgat1 Genesmentioning
confidence: 99%
“…In addition, more than 40% of the total amino acid residues are hydrophobic (Table 3). Yeast was the preferred host for DGAT expression (Bouvier-Nave et al, 2000;Burgal et al, 2008;Cao et al, 2010;He et al, 2004;Kalscheuer et al, 2004;Kalscheuer & Steinbuchel 2003;Kroon et al, 2006;Liu et al, 2011;Liu et al, 2010;ManasFernandez et al, 2009;Mavraganis et al, 2010;Milcamps et al, 2005;Nykiforuk et al, 2002;Quittnat et al, 2004;Shockey et al, 2006;Siloto et al, 2009;Wagner et al, 2010;Xu et al, 2008;Yu et al, 2008) followed by insect cells (Buszczak et al, 2002;Cases et al, 1998;Cases et al, 2001;Lardizabal et al, 2001). A limited number of reports used other host cells including E. coli (Saha et al, 2006;Siloto et al, 2008;Weselake et al, 2006) and human cells (Cheng et al, 2001).…”
Section: Recombinant Dgat Expression Updatementioning
confidence: 99%
“…Animals with reduced DGAT activity are resistant to diet-induced obesity Smith et al, 2000) and lack milk production (Smith et al, 2000). Over-expression of DGAT enzymes increases TAG content in plants (Andrianov et al, 2010;Bouvier-Nave et al, 2000;Burgal et al, 2008;Durrett et al, 2010;Jako et al, 2001;Lardizabal et al, 2008;Xu et al, 2008), animals (Kamisaka et al, 2010;Liu et al, 2009;Liu et al, 2007;Roorda et al, 2005), and yeast (Kamisaka et al, 2007). DGATs have nonredundant functions in TAG biosynthesis in species such as mice (Stone et al, 2004) and tung tree (Vernicia fordii) (Shockey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%